2019
DOI: 10.3390/technologies7010019
|View full text |Cite
|
Sign up to set email alerts
|

On Distributed Denial of Service Current Defense Schemes

Abstract: Distributed denial of service (DDoS) attacks are a major threat to any network-based service provider. The ability of an attacker to harness the power of a lot of compromised devices to launch an attack makes it even more complex to handle. This complexity can increase even more when several attackers coordinate to launch an attack on one victim. Moreover, attackers these days do not need to be highly skilled to perpetrate an attack. Tools for orchestrating an attack can easily be found online and require litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…1, right). While in 2018 a DDoS attack was peaking 1.7 TBit/s in traffic volume on GitHub servers, the frequency of DDoS attacks also increased more than 29.7% times between 2015 and 2016 [8]. However, the 52% reduction in the number of large-scale attacks from…”
Section: Botnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, right). While in 2018 a DDoS attack was peaking 1.7 TBit/s in traffic volume on GitHub servers, the frequency of DDoS attacks also increased more than 29.7% times between 2015 and 2016 [8]. However, the 52% reduction in the number of large-scale attacks from…”
Section: Botnetsmentioning
confidence: 99%
“…Akamai reported that the majority of attacks ranged between 250 Mbit/s and 1.25 Gbit/s in traffic volume. However, in 2018 there was an alarming increase in the number of large-scale attacks by 67.1% due to different Mirai variations and reflection attacks based on Memcached [8].…”
mentioning
confidence: 99%
“…Recently, various proposed solutions based on machine learning (ML) to detect DoS and DDoS have been proposed in the literature, such as the unsupervised clustering model, the Linear Vector Quantization (LVQ) model of Artificial Neural Network (ANN), and the Back-Propagation (BP) model of ANN. A pertinent classifier based on Support Vector Machine (SVM) to detect and prevent DDoS TCP flooding attacks upgrades the K-nearest, naive Bayes, and multilayer perceptron in terms of performance [51]. Finally, one effective solution against the MQTT exploit is to secure the MQTT protocol by implementing the attribute-based encryption through the elliptic curve [52].…”
Section: Security Threats and Solutionsmentioning
confidence: 99%
“…However, there is very little literature focusing on characterizing and proposing defense mechanisms targeting these tools. Most studies also focus on tools no longer in use [13]. Very few discussed current DoS attack tools.…”
Section: Related Workmentioning
confidence: 99%
“…Though such tools have been available for years, there has been no defense mechanism proposed specifically targeting these tools. Most defense mechanisms in literature are designed to defend attacks captured in datasets like the KDD Cup 99 dataset from 20 years ago and from tools no longer in use in modern attacks [13]. Knowledge of traffic features of current DoS attack tools is also not available.…”
Section: Introductionmentioning
confidence: 99%